Thymoquinone Pectin Beads Produced via Electrospray: Enhancing Oral Targeted Delivery for Colorectal Cancer Therapy - Mulham Alfatama; Hazem Choukaife; Okba Al Rahal; Nur Zahirah Mohamad Zin (MDPI AG, 2024)
Background/Objectives: Thymoquinone (TQ) exhibits diverse biological activities, but its poor solubility and bioavailability limit its cancer efficacy, requiring innovative solutions. This study explores the development of an oral delivery system targeting colon cancer based on TQ pectin beads (TQ-PBs) produced through an adjustable electrospray technique. This study hypothesised that adjusting bead diameter through the electrospray technique enables precise control over water absorption and erosion rates, thereby achieving a controlled release profile for encapsulated TQ, which enhances targeted delivery to the colon. Methods: TQ-PBs were synthesised and optimised using an electrospray technique based on the ionic gelation method. The prepared beads were characterised based on particle size, sphericity, encapsulation efficiency (EE), water uptake, erosion, surface morphology, molecular interactions, and texture. The cumulative TQ release studies, an accelerated stability test, and cytotoxicity evaluation against the colon cancer HT-29 cell line were also assessed. Results: The optimised TQ-PB formulation demonstrated an average bead size of 2.05 ± 0.14 mm, a sphericity of 0.96 ± 0.05, and an EE of 90.32 ± 1.04%. The water uptake was 287.55 ± 10.14% in simulated gastric fluid (SGF), 462.15 ± 12.73% in simulated intestinal fluid (SIF), and 772.41 ± 13.03% in simulated colonic fluid (SCF), with an erosion rate of 45.23 ± 5.22%. TQ release was minimal in SGF (8.13 ± 1.94% after 2 h), controlled in SIF (29.35 ± 3.65% after 4 h), and accelerated in SCF (94.43 ± 2.4% after 3 h). Stability studies over one month showed a size reduction of 17.50% and a 6.59% decrease in TQ content. Cytotoxicity assessments revealed significant anticancer activity of TQ-PB, with an IC50 of 80.59 ± 2.2 μg/mL. Conclusions: These findings underscore the potential of TQ-PB as an effective oral drug delivery system for targeted colorectal cancer therapy.